2003
DOI: 10.1080/713608372
|View full text |Cite
|
Sign up to set email alerts
|

PPARα Agonist-Induced Rodent Tumors: Modes of Action and Human Relevance

Abstract: Widely varied chemicals--including certain herbicides, plasticizers, drugs, and natural products--induce peroxisome proliferation in rodent liver and other tissues. This phenomenon is characterized by increases in the volume density and fatty acid oxidation of these organelles, which contain hydrogen peroxide and fatty acid oxidation systems important in lipid metabolism. Research showing that some peroxisome proliferating chemicals are nongenotoxic animal carcinogens stimulated interest in developing mode of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
347
1
9

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 562 publications
(375 citation statements)
references
References 404 publications
15
347
1
9
Order By: Relevance
“…Hepatic peroxisome proliferation is considered to be strong proof of PPARα 11 activation in rats and mice [25], and has been used as an important standard to estimate susceptibility to rodent HCC in the development of new candidate compounds with PPARα activation and serum lipid-lowering activity. However, the present results indicate that peroxisome proliferation is not necessarily a suitable biological marker of continuous PPARα activation.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic peroxisome proliferation is considered to be strong proof of PPARα 11 activation in rats and mice [25], and has been used as an important standard to estimate susceptibility to rodent HCC in the development of new candidate compounds with PPARα activation and serum lipid-lowering activity. However, the present results indicate that peroxisome proliferation is not necessarily a suitable biological marker of continuous PPARα activation.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds have been the subject of debate for several decades because of their carcinogenicity in rodents (Lalwani et al, 1981) and uncertain risk to humans (Klaunig et al, 2003;Rusyn et al, 2006). A number of peroxisome proliferator-induced events leading up to carcinogenesis, including increased cell replication, oxidative damage and tumorigenesis itself require activation of nuclear receptor peroxisome proliferators-activated receptor alpha (PPARα) (Peters et al, 1997;Rusyn et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…There are also data showing that the liver toxicity/carcinogenicity induced by SCCP is associated with peroxisome proliferation, whereas the thyroid effects are correlated to altered thyroid hormone homeostasis. A number of scientific working groups, including the International Agency for Research on Cancer (IARC), have concluded that liver tumors induced by peroxisome proliferators are not relevant to humans (IARC, 1990;Klaunig et al, 2003). Humans are expected to be much less sensitive to thyroid hormone perturbation than rats and mice.…”
Section: Human Health Effectsmentioning
confidence: 99%